For the first problem, integration by parts is not needed. Just let u = x-5.
For the second problem, you made a sign error somewhere.
i think this is integration by parts with u = x and dv = x-5 is this correct?
e^(2x) * sinx dx
u = sinx dv = e^(2x)
i end up doing integration by parts 1 time and then i find i have to do it again
after the 2nd integration of parts i end up with.......
(sinx)(e^(2x))-(cosx)(e^(2x)) + integral of | e^(2x)(sinx)
the problem is the bolded part is the original equation...but when i move it to the other side it cancels out the problem...i have no idea what i am doing wrong -thx